Estimation of Principal Induced Stresses in Longwall Faces through Seismic Moment Tensor Inversion - Mahdevari, Sattar; Shahriar, Kourosh; Sharifzadeh, Mostafa (2017)
Summary: Induced stresses and various instabilities and deformations are resulted due to stress concentrations around a longwall face. A considerable part of the induced stresses is transferred ahead of the face and onto the adjacent T–junctions and gate roadways, which creates a zone of high stress that advances with the face advancement. A nondestructive examination based on the Seismic Moment Tensor (SMT) inversion was presented to estimate the direction of principal induced stresses around active longwall panels. The E2 longwall panel at Tabas coal mine was selected as a case study. Introduction: The induced stresses in front of the coalface can cause fractures to initiate and propagate, which in turn, lead to roof collapse. This phenomenon causes considerable problems in the face area and adjacent workings. The SMT solutions were presented for 24 seismic events at Tabas mine, which result in roof collapses and long delays in production. Most of the events occurred in the vicinity of the longwall face. The seismic waves generated during face advancement are used to estimate the SMTs through the process of SMT inversion. Methodology and Approaches: SMT inversion is the best method to calculate SMT from the recorded seismic parameters. The trick in the SMT inversion is to use long–period (low frequencies) regional distance seismic waves. The source process can be reduced to a simple delta function in space and time. The wave propagation is also simplified because filtering regional seismograms to long–periods, results in waves that have only propagated in a few wavelength cycles that can be easily predicted using relatively simple 1D layered earth models. The mathematical code is developed in MATLAB software to estimate the best solution for SMT. The resulted SMTs are decomposed in terms of its principal axes based on the eigenvalues and the directions of the eigenvectors. The directions of the principal induced stresses are then obtained based on the eigenvalues and the corresponding eigenvectors. Results and Conclusions: According to the results, it can be conceivable that roof falls similar to collapse of the immediate roof strata within the face area may be produced by compressive/tensile failure mechanisms, which result from stress concentration and gravitational forces. These are in accordance with the directions of the principal induced stresses, which obtained based on the eigenvalues and the corresponding eigenvectors. On the other hand, the shear failures are mainly resulted around the preexisting planes of weakness such as faults that intersected the coalface or excavation boundaries. In general, the maximum principal induced stress in all 24 events is mostly oriented with an acute angle with respect to horizon. This shows that the dominancy of horizontal induced stresses in occurrence of roof failures and face instabilities.